Cardiological Support in Neonatal Surgery: Modern Approaches to The Correction of Congenital Heart Anomalies - Magomedovna Abdurakhmanova, Asiyat; Abakaraskhabovna Kasumova, Malikhat; Abdurakhmanovna Muhuchaeva, Patimat; Shakhmuradovna Mamerzaeva, Arina; Khasaevna Yunusova, Anzhelika; Robertovna Dorosheva, Mariya; Denisovna Sazhina, Elizaveta (Journal of Neonatal Surgery, 2025)
The article reviews modern approaches to cardiological support in surgical treatment of congenital heart disease in newborns. Special attention is paid to the integration of neonatal cardiology and surgery to improve the efficiency of diagnosis, preparation for surgery and postoperative management of patients. Advanced prenatal diagnostic techniques, such as three- and four-dimensional echocardiographic studies, are discussed, as well as the role of multimodal technology in assessing the severity of anomalies and planning surgical intervention. The article analyses the use of minimally invasive techniques for defect correction, including catheter-based technologies and stenting, which can reduce the risk of complications and improve prognosis in newborns with critical heart defects. The importance of a multidisciplinary approach is emphasised, where cardiologists, surgeons, anaesthesiologists and neonatologists work together to ensure optimal management of the patient's condition at all stages of treatment. In addition, data are presented on the role of supportive therapies, including extracorporeal membrane oxygenation (ECMO) and other life support methods, which are becoming an integral part of treatment protocols for complex congenital heart anomalies. The prospects for the development of genetic diagnostics and personalised medicine in the context of prevention and correction of neonatal heart defects are considered.